Cognitive versatility and adaptation to fluid participation in hospital emergency department teams - Aggarwal, Ishani; Mayo, Anna T.; Murase, Toshio; Zhang, Evelyn Y.; Aven, Brandy; Woolley, Anita Williams (Frontiers in Psychology, 2024)
Role-based frameworks have long been the cornerstone of organizational coordination, providing clarity in role expectations among team members. However, the rise of “fluid participation”—a constant shift in team composition and skill sets—poses new challenges to traditional coordination mechanisms. In particular, with fluid participation, a team’s roles can oscillate between disconnected and intersecting, or between lacking and having overlap in the capabilities and expectations of different roles. This study investigates the possibility that a disconnected set of roles creates a structural constraint on the flexible coordination needed to perform in volatile contexts, as well as the mitigating role of cognitive versatility in a team’s strategically-central member. Utilizing a sample of 342 teams from a hospital Emergency Department, we find that teams with a disconnected role set are less effective than teams with an intersecting role set as demonstrated by longer patient stays and increased handoffs during shift changes. Importantly, the presence of a cognitively versatile attending physician mitigates these negative outcomes, enhancing overall team effectiveness. Our findings remain robust even after accounting for other variables like team expertise and familiarity. This research extends the Carnegie School’s seminal work on fluid participation by integrating insights from psychology and organizational behavior, thereby identifying key individual attributes that can bolster team coordination in dynamic settings.